Analisis Faktor Content Iklan Online untuk Meningkatkan Profitabilitas Perusahaan Menggunakan Partial Least Square (Studi Kasus Pada OLX.CO.ID) - Husin Husin (Puslitbang Sinergis Asa Professional, 2021)
The development of the Internet in this day and age is happening rapidly, including the lifestyle of consumers in meeting their daily needs. So that the internet as an advertising medium is based on the aspects of convenience and more benefits offered by the internet, namely the ease of information dissemination, wide reach, and easy access from consumers to advertisements on the internet. The purpose of this study is to examine and analyze the effect of judgment of online advertisement on attitude towards online advertisement, feelings of online advertisement on attitude towards online advertisement, attitude towards online advertisement towards attitude towards brand, and attitude towards brand towards purchase intention. The research method uses a quantitative approach, with the type of causal research. The data used in this study is primary data. The analysis technique used is Partial Least Square (PLS).